Immunogenicity and safety of purified vero cell-cultured rabies vaccine under Zagreb 2-1-1 or 5-dose Essen regimen in the healthy Chinese subjects: a randomized, double-blind, positive controlled phase 3 clinical trial. Issue 2 (1st February 2021) - Shen, Heng; Wang, Zhao; Yang, Beifang; Cai, Kun; Jiang, Changjun; Xie, Ronghua; Xiao, Haitao; Ren, Qunhui; Qi, Zhengxu; Li, Jinghui; Li, Qiong; Ye, Jianjun; et al.
ABSTRACT: Aim : The aims of the study were to evaluate the non-inferiority of the safety and immunogenicity of a new trial purified vero cell-cultured rabies vaccine (trial vaccine) in healthy subjects comparing with the control purified vero cell-cultured rabies vaccine (control vaccine) following Essen regimen and to evaluate the non-inferiority of the safety and immunogenicity of the trial vaccine following two intramuscular regimens, between Zagreb and Essen regimen. Methods : Serum samples were collected before vaccination and on d 7, 14, 35/42 post vaccination. Adverse events (AEs) were recorded for 30 d following each vaccination. This study was registered in the Chinese Clinical Trial Registry (ChiCTR-PPR-15007057). Results : There was no significant difference in the incidence of AEs, local and systemic reactions, among Zagreb group, Essen group, and control group. But the incidence of solicited AEs was a significant difference among the three groups ( p = 0.0498). The incidence of solicited AEs was higher in Essen group than that in control group and Zagreb group ( p = 0.0278, p = 0.0248). In the subjects whose antibodies were seronegative before vaccination, the seroconversion rates of antibodies among three groups were all 100.0% on d 14 and d 35/42. The Essen group was not inferior to the control group, and the Zagreb group was not inferior to the Essen group on d 14. On d 14 and d 35/42, the geometric mean concentration of the three groups was much higher than the immune protection level of 0.5 IU/ml. Conclusions : The trial vaccine had good safety and immunogenicity, and the trial vaccine is not inferior to the control vaccine. Abbreviations: PVRV: purified vero cell-cultured rabies vaccine; AE: adverse event; CI: confidence interval; GMC: geometric mean concentration; IM: intramuscular; NIFDC: National Institutes for Food and Drug Control; PPS: per-protocol set; SS: safety set; REFIT: Rapid Fluorescent Focus Inhibition Test; RVNA: rabies virus neutralizing antibody; WHO: World Health Organization.